Field parasitism of Rhinocyllus conicus Froelich (Coleoptera Curculionidae) by Microctonus aethiopoides Loan (Hymenoptera Braconidae) in Otago and South Canterbury - Murray, T.J.; Barratt, B.I.P.; Ferguson, C.M. (New Zealand Plant Protection, 2002)
Microctonus aethiopoides was first recorded parasitising the weed biocontrol agent Rhinocyllus conicus in 1994 Subsequent studies found parasitism at several sites in Otago and South Canterbury In this study a further 15 sites in Otago and South Canterbury were sampled to determine the extent and level of parasitism of R conicus by M aethiopoides Rhinocyllus conicus adults were collected from nodding thistles and were either reared or dissected to determine parasitism levels For dissected weevils the stages of parasitoid development presence of teratocytes weevil size and female weevil reproductive status were recorded Parasitism was recorded at 12 sites Lucerne the host plant of the weevil Sitona discoideus for which M aethiopoides was originally introduced into New Zealand was absent from most of these sites Levels of parasitism were similar to those recorded in previous studies reaching up to 17 in the Hakataramea Valley Results relating to weevil size and female weevil reproductive state are discussed